Komparasi antara Konsep Syura dan Demokrasi dalam Politik Islam - Toguan Rambe; Seva Mayasari (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This paper examines the concept of Shura and democracy in a normative manner and then in depth the interesting things in a comparative study. This study stems from a prolonged discussion among Muslim intellectual circles about the full picture of Islamic politics. In general, contemporary Muslim scholars and intellectuals make the concept of shura or deliberation as a principle in the study of Islamic politics. This could be the actualization of Islamic teachings by arguing that the democratic system is substantially in line with Islam and has become a major theme in the development of a civilized political system. The substantial values of democracy that are in line with Islam can be observed from the thinking of political experts. Whereas Islam as a universal religion includes the principles that support the establishment of democracy, namely the principles of justice, equality, equal rights and obligations before the law, pluralism, equalitiy, liberty and the principle of deliberation. However, implementatively these substantial values do not escape the tiring problems and discourse, which cannot be separated from the existence of Islam with comprehensive teachings in all aspects, in contrast to Western values based on secularism and freedom.